Novas tecnologias para o controle da giberela do trigo na safra 2014 no sudoeste do Paraná - Butrinowski, Ricardo Tavares (2015)
The work consists in wheat production system and the evolution of damage caused by wheat scab. The study considers the lack of resistant cultivars to the disease, the low efficiency of chemical control and the presence of mycotoxins in grains. The study aimed to confirm the effectiveness of fungicides prothioconazole and metconazole; prove the bar deposition efficiency with nozzles directed jets the side of the ear resulting in full coverage of trapped anthers; prove the viability of using a warning system (application after the start of flowering before the onset of rains provided for future 24-48 hours and try to improve the efficiency in controlling scab. The experiment was conducted in the experimental field of Technological University Federal do Paraná in the city of Pato Branco, Paraná, conducted in two seasons, the first established on May 6, 2014 and the second on 21 May 2014. It was used to cultivate Amethyst field of OR Improvement seeds, . Passo Fundo, Rio Grande do Sul Treatments consisted of a control without fungicide application and one and two applications of prothioconazole + 17.5% trifloxystrobin (Fox) 500 ml / ha; metconazole 8.0% + pyraclostrobin 13% ( Opera Ultra) 750 mL / ha In the evaluation, second season, metconazole + pyraclostrobin with two application statistically was the treatment that showed a lower incidence in spikes reducing from 100 to 63.3%;. metconazole + pyraclostrobin performed better also in reducing the incidence of spikelets, 80.3% to 34.7%; the control ears had better results in the second season with two applications of metconazole + pyraclostrobin; in spikelets, in his first season, metconazole + pyraclostrobin with two application resulted in better control with 67%; with two applications of metconazole + pyraclostrobin gave the highest yield even under climatic conditions favorable to disease; metconazole + pyraclostrobin in both seasons showed superior efficiency in controlling FHB giving greater weight gain; with two application of both fungicides, the hectoliter weight was 81 and 79, respectively, each fungicide; the application of fungicides was made in advance of expected rain, occurring seven days of rain and a total volume of 85,2mm the first time, and 16 days of rain and an accumulation of 400 mm in the second period; the test efficiency can be confirmed when the direction of the spray jets launched wings coupled in double nozzle bodies perpendicular to the target upright reaches the sides of the spike. The metconazole + pyraclostrobin proved the most effective fungicide against the prothioconazole + trifloxystrobin in wheat scab control in the 2014 harvest.